2020
DOI: 10.1007/s00062-020-00980-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Thrombectomy for Acute Intracranial Carotid Occlusion with Patent Intracranial Arteries

Abstract: Purpose Intracranial carotid artery occlusion represents an underinvestigated cause of acute ischemic stroke as well as an indication for mechanical thrombectomy. We investigated baseline and procedural characteristics, outcomes and predictors of outcome in patients with acute ischemic stroke secondary to intracranial carotid artery occlusion. Methods A retrospective analysis of the Italian Registry of Endovascular Treatment in Acute Stroke was performed. Patients with intracranial carotid artery occlusion (in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…Furthermore, this factor affects the mortality rate, which was 2% in the rst group and 33% in the second group (p = 0.015). This data is in accordance with a previous study which found a correlation between recanalization and outcome in acute ischemic stroke: recanalization is strongly associated with improved functional outcome and reduced mortality [19,33].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, this factor affects the mortality rate, which was 2% in the rst group and 33% in the second group (p = 0.015). This data is in accordance with a previous study which found a correlation between recanalization and outcome in acute ischemic stroke: recanalization is strongly associated with improved functional outcome and reduced mortality [19,33].…”
Section: Discussionsupporting
confidence: 93%
“…Accounting for 4% of anterior large vessel occlusions, the rate of patients with isolated ICA occlusion treated in our centers was consistent with the MERCI and Multi-MERCI analyses but lower than the rate (7.8%) reported by the Italian Registry of Endovascular Treatment in Stroke [ 6 , 13 ]. Compared with the MR CLEAN and REVASCAT trials [ 4 , 5 ], these rates indicate the higher likelihood of facing a patient with AIS due to isolated ICA occlusion in a real-world setting.…”
Section: Discussionsupporting
confidence: 89%
“…Recently, one study investigated the benefit of initial BMT in patients with isolated ICA occlusion and reported a favorable outcome in 69% [ 11 ]. This rate is notably higher than that of 2 recent thrombectomy studies, which reported 34% and 26% favorable outcomes, respectively [ 12 , 13 ]; however, this difference in outcomes is likely attributable to variations in the median baseline National Institutes of Health stroke scale (NIHSS) scores.…”
Section: Introductionmentioning
confidence: 64%
“…[1][2][3][4][5][6][7][8][9][10] On the other hand, compared with TFA, TRA has been shown to have the following drawbacks: increased radiation exposure due to prolonged operation time; 8 difficulty performing the procedure for anatomic reasons; 4 a lack of TRAspecific devices; and the need for proficiency in the procedure. 2,[11][12][13][14] However, the majority of the literature comparing TRA and TFA is based on reports of diagnostic cerebral angiography, [15][16][17][18][19][20][21] carotid stenting, [22][23][24] vertebral and basilar artery stenting, 25 mechanical thrombectomy, [26][27][28][29] and flow diversion, 30,31 with few studies on intracranial aneurysms.…”
Section: Introductionmentioning
confidence: 99%